Retailing: An Emerging Trend in India - Gupta, C. P.; Chaturvedi, Mitali (Indian Journal of Marketing, 2007)
Retailing encompasses the business activities involved in setting goods and services to their consumers for their personal family or household use. It includes very sale to the final consumers ranging from cars to apparel, to meals at restaurant to theater tickets (Berman&Evans). Retail is the largest private industry in the world with total sales of 6.6% trillion. This industry accounts for 8% of the GDP in the western economics and has generated an 18% return for shareholders between 1994 and 1999 as compared to banks while generate a 9% percent return and insurance which generated a 15.2 percent return (Indian Retail Report end February 2002 Pg 21). The fact that the largest corporation in the world, Wal-Mart is a retail chain, only confirms the significance of this industry (Fortune, July 2002). The retail sector plays a significant role in the world economy because of the contribution that it makes to the economy of the country.